EKSLUSIFITAS KEBERAGAMAAN WARIA PEKERJA SALON KOTA PADANG - Sudarman Sudarman; Lukmanul Hakim (Kafa`ah: Journal of Gender Studies, 2015)
Transvestites are always identified as God's creatures are far from religion, even more extream is  an attitude to life that challenges the will of God. This perception has been inherited from generation to generation making transvestites as people marginalized in society. The study wants to answer academic anxiety about how the religiousity of transsexual beauty salons worker in the city of Padang. The study used a qualitative research method, in which the collected data to rely on in-depth interviews as well as continuous observation so get data that can be accounted for by an academic. To analyze the data, using descriptive data that will show and describe the facts and nature of the informant  based on the  understanding and religious activity of transvestite.The result are; 1) The religious knowledge of transsexual beauty salons worker in Padang city is divided into three categories; high, moderate and low. 2) Religious practice of transsexual beauty salons worker in the city of Padang is divided into three, namely: transvestite salon workers who have a religious practice strong, moderate and weak.